Proceso de atención de enfermería en un neonato con atresia pulmonar. - Banchon Nivela, Jennifer Elizabeth (2020)
The clinical case study of pulmonary atresia in a 30-day-old neonate, in the pediatric area of the General Guasmo Sur Hospital in the city of Guayaquil, this being a genetic alteration that compromises the life of the neonate; Our objective of this study is to develop the nursing care process and establish the diagnoses and interventions that improve their quality of life. The cause of this pathology is not known. Pulmonary atresia is a heart defect that endangers the life of the newborn; Because the valve that allows blood to leave the heart and go to the baby's lungs has not formed properly. The assessment is carried out using the functional patterns of the model of the theorist Marjory Gordon, to identify the patterns that are affected and to be able to meet the needs that are within our scope of nursing, through a care plan, prioritizing those needs that require be treated immediately and reduce the risk of further complications.